A Review: Hydro Turbine in Hydraulics System(Pipe-Line) to Generate Electricity(Renewable Energy) - Mohd Aminuddin, Nur Azmina; Tan, Lai Wai (Recent Trends in Civil Engineering and Built Environment, 2024)
Energy has become one of the important needed in this era. There are many kinds of ways to gain sources of energy, whether it is renewable or non-renewable energy. Renewable energy is more eco-friendly than non-renewable energy. Hydro power is classified as a renewable energy source. As humans are using water in pipe everyday in their life cycle, this flowing water with high pressure can be used to create electrical energy using the water turbine concept in the pipeline. Where a small turbine generator can be plug into the pipeline so that the kinetic energy due to flowing water can become electrical energy. However, to gain energy from this method, it is important to properly operate the operation so that maximum energy can be produced. In now era, hydro power turbine in pipeline had gain more interest as it had low environmental impacts. In 2008, a group of frameworks called HYLOW, had made a first prototype of water turbine in pipeline has been made using CFD analysis and been tested. Where found that validation and optimizing are still required. Then after a time, another prototype was made where it had around 60% efficiencies in low-headed operation that below 5 meters. A water turbine in pipeline is called small hydro power and been classified in mini, micro or pico. It is classified depends on the energy it vans produced. However, the class is still not use globally, where it is depends on the country. Propeller turbine is chosen in this review as it designed is suitable for high head flow water and pipe condition.